2017
DOI: 10.1016/j.str.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis Reveals Features of Ribosome Assembly Factor Nsa1/WDR74 Important for Localization and Interaction with Rix7/NVL2

Abstract: SUMMARY Ribosome assembly is a complex process that requires hundreds of essential assembly factors, including Rix7 (NVL2 in mammals) and Nsa1 (WDR74 in mammals). Rix7 is a type-II double ring, AAA-ATPase, which is closely related to the well-known Cdc48/p97. Previous studies in Saccharomyces cerevisiae suggest that Rix7 mediates the release of Nsa1 from nucleolar pre-60S particles however the underlying mechanisms of this release are unknown. Through multiple structural analyses we show that S. cerevisiae Nsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…This solvent-side location of Nsa1 explains why failure of its removal during 60S biogenesis, due to an N-terminal deletion in the Rix7 AAA ATPase, still allows the formation of functional 80S ribosomes and polysomes ( Kressler et al., 2008 ). The loop between the fourth and fifth β-blade of Nsa1 (Loop 4D-5A) ( Figure 2 A) was described to mediate the interaction between the human homologs of Nsa1 (WDR74) and Rix7 (NVL2) ( Lo et al., 2017 ). Yet in yeast, we found that the Nsa1 loop 4D-5A is involved in interactions with ES7a and Mak16; it is therefore not readily accessible for interaction with Rix7 ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…This solvent-side location of Nsa1 explains why failure of its removal during 60S biogenesis, due to an N-terminal deletion in the Rix7 AAA ATPase, still allows the formation of functional 80S ribosomes and polysomes ( Kressler et al., 2008 ). The loop between the fourth and fifth β-blade of Nsa1 (Loop 4D-5A) ( Figure 2 A) was described to mediate the interaction between the human homologs of Nsa1 (WDR74) and Rix7 (NVL2) ( Lo et al., 2017 ). Yet in yeast, we found that the Nsa1 loop 4D-5A is involved in interactions with ES7a and Mak16; it is therefore not readily accessible for interaction with Rix7 ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to binding Mak16, Rpf1 also binds L32, Nsa1 and the base of helix ES7a. Nsa1 contains a WD domain (Lo et al, 2017 ) and is docked at H19, ES7a and Rpf1. Rrp1 folds into a super-helical structure and contacts L4, L18, the N-terminus of L7, Mak16 and RNA helix ES7a.…”
Section: Resultsmentioning
confidence: 99%
“…The unmodeled density was assigned with assistance of the BALBES-MOLREP pipeline (Brown et al, 2015 ) and CXMS data. The crystal structures of the Brx1 and Ebp2 complex determined here and the Nsa1 structure (Lo et al, 2017 ) were fitted as rigid body. Homology models of Rpf1 and Has1 were created by SWISS-MODEL (Biasini et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…New assembly factors Mak16, Rrp1, Nop16, Erb1-NTD, Rrp14, Rrp15 and Ebp2 and segments of rRNA were modelled de novo . Previously determined crystal structures of assembly factors Nsa1 (PDB 5SUI) 26 , Ytm1 (PDB 5CXB) and Erb1-CTD (PDB 4U7A) 27 were docked and manually adjusted. Has1, Ssf1, Brx1, Rpf1 and Mak11 were initially docked from Phyre2 models 28 , and manually built to fit the density.…”
Section: Methodsmentioning
confidence: 99%